Efficient adsorption of organic dyes using Fe3O4/carbon sphere nanocomposites: Synthesis and performance evaluation - Ta Duc Khue; Pham Kim Ngoc; Do Thanh Viet; Tran Dang Thanh; Tuan Hong Nguyen; Pham Van Vinh; Dinh Lam Nguyen; Pham Duc Thang; Anh Tuan Duong; Raja Das; Huu Tuan Nguyen (Journal of Science: Advanced Materials and Devices)
This study reports the synthesis of Fe3O4/carbon sphere (CS) nanocomposites via a solvothermal method followed by co-precipitation for the efficient adsorption of organic dyes. The structural and morphological characteristics of the nanocomposites were analyzed using scanning electron microscope, X-ray diffraction, and energy-dispersive X-ray spectroscopy, confirming the successful integration of Fe3O4 nanoparticles onto the CS surface. Adsorption kinetics followed the pseudo-second-order model, suggesting chemisorption as the primary mechanism for methylene blue (MB) and rhodamine B (RB) dye removal. The adsorption process aligned well with the Langmuir isotherm model, with optimized nanocomposites achieving nearly 100 % removal of MB and RB within just 5 min. In contrast, Fe3O4 nanoparticles showed poor adsorption, removing less than 10 % of MB and 24 % of RB after 120 min, whereas CS removed 93.5 % of MB and 73 % of RB in the same timeframe. Featuring strong magnetic properties for easy separation, high stability, and exceptional adsorption efficiency, Fe3O4/CS nanocomposites emerge as promising reusable adsorbents for wastewater treatment.